A NEW SUBSPECIES OF SENECIO MOHAVENSIS (COMPOSITAE) REVEALS OLD–NEW WORLD SPECIES DISJUNCTION - COLEMAN, M.; FORBES, D. G.; ABBOTT, R. J. (Edinburgh Journal of Botany, 2001)
Examination of morphology, ploidy and interfertility in the two subspecies of the Old World Senecio flavus (Decne.) Sch. Bip. (Compositae) and the closely related New World S. mohavensis A. Gray does not support the subspecific taxonomy of S. flavus. On the basis of our results S. flavus subsp. breviflorus Kadereit is transferred to S. mohavensis as a new subspecies: S. mohavensis subsp. breviflorus (Kadereit) M. Coleman comb. nov. The new subspecies has a distribution that includes Arabia, the Middle East, Sinai, Iran, Afghanistan, Djibouti, and the Thar Desert of Pakistan. The type subspecies of S. mohavensis occurs in the Mojave and Sonoran deserts of North America, providing an unusual disjunct distribution at the species level. Separation from S. flavus is based upon differences in morphology and chromosome number. Senecio flavus is diploid (2n = 20), while both subspecies of S. mohavensis are tetraploid (2n = 40). Further support for the new taxonomic treatment is provided by the results of controlled crosses. No artificial hybrids have been generated from crosses made between the previously recognized subspecies of S. flavus, while crosses between the newly recognized subspecies of S. mohavensis have produced fertile hybrids. The fertility of the hybrids is significantly lower than the parental taxa (P
Keywords: Asteraceae; long-distance dispersal; polyploidy; Senecio flavus